A resected case of lung metastasis of the reconstructed gastric tube cancer after radical operation for esophageal cancer - Nakagawa, Ken; Okumura, Sakae; Tsuchiya, Sigehiro; Hiramatsu, Kiyoshi; Iijima, Keita; Matsubara, Toshiki (Nihon Kokyuki Geka Gakkai zasshi (Kyoto, 1992), 1999)
Here we report a resectable case of lung metastasis from reconstructed gastric tube cancer after radical operation for esophageal cancer. A 63-year-old man underwent esophagectomy with reconstruction with a gastric tube through the antesternal route for a thoracic esophageal cancer in 1988. On follow up in our hospital serum CEA levels were as high as 18.4 ng/ml with no complaint in 1995. Endoscopic examination revealed Borrman type 1 cancer in the lower part of the gastric tube. Partial resection of the gastric tube and D2 lymph node dissection were performed. Serum CEA level decreased to within normal limits after the operation. In 1998 chest CT revealed a round mass shadow 5 × 5 mm in size in upper lobe S1a of the right lung with serum CEA level elevating again to as high as 16.6 ng/ml. Three months later chest CT was performed again and showed a mass shadow growing to 12 × 10 mm in size with parallel elevation of serum CEA level. We diagnosed lung metastasis of the reconstructed gastric tube cancer. Partial resection of the right lung was performed in 1998. Resected specimen was histologically diagnosed as well differentiated tubular adenocarcinoma compatible with a lung metastasis of the gastric tube cancer. In the Japanese and English literature this is the first case report of resection of lung metastasis from gastric tube cancer.